2021
DOI: 10.1029/2021jb022622
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependent Mantle Viscoelasticity via the Complex Viscosity: Cases From Antarctica

Abstract: The growth and decay of ice sheets over the Pleistocene represent large variations in Earth's climate system and induce significant deformation of the solid Earth. This deformation (including associated changes to Earth's stress and gravity field, and its rotation axis), in response to the redistribution of ice and ocean mass, is known as "glacial isostatic adjustment" (GIA). Areas that were formerly covered by or close to major ice sheets during the last glacial period, such as Fennoscandia, Greenland, North … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 116 publications
0
27
0
Order By: Relevance
“…Such rheological complexity may also contribute to, or even generate, confined regions with effectively low viscosity, of the sort that we have modeled here. Regardless, the impact of rheological complexity needs more investigation and could help to reconcile models and observations of uplift (Adhikari et al, 2021;Blank et al, 2021;Lau et al, 2021). Bevis et al (2012) found that in most of coastal Greenland the elastic response to contemporary ice mass change matches the historic viscous response or dominates the uplift signal.…”
Section: Factors Affecting Uplift From Contemporary Ice Meltmentioning
confidence: 99%
See 1 more Smart Citation
“…Such rheological complexity may also contribute to, or even generate, confined regions with effectively low viscosity, of the sort that we have modeled here. Regardless, the impact of rheological complexity needs more investigation and could help to reconcile models and observations of uplift (Adhikari et al, 2021;Blank et al, 2021;Lau et al, 2021). Bevis et al (2012) found that in most of coastal Greenland the elastic response to contemporary ice mass change matches the historic viscous response or dominates the uplift signal.…”
Section: Factors Affecting Uplift From Contemporary Ice Meltmentioning
confidence: 99%
“…For example, several studies focused on similar locations have resulted in different estimates for mantle viscosity and lithosphere thickness based on historical sea level data and present-day deformation. Lau et al (2021) argued that these different estimates result from different timescales of deformation and that transient, frequency-dependent, rheology may play an important role on GIA timescales. Kang et al (2022) showed that stress-dependent rheology causes temporal variations in upper mantle viscosity due to stress variations during the last deglaciation (ended 8,000 years ago), and that the effects can be rather localized (i.e., affecting load-proximal stresses but not far field stresses).…”
Section: Factors Affecting Uplift From Contemporary Ice Meltmentioning
confidence: 99%
“…It is still an open question as to whether stressdependent viscosity and transient viscosity need to be included in geodynamic models (Ivins et al 2021). In the latter case, is considering short-term and long-term viscosity sufficient or does viscosity need to be considered as a function of loading frequency (Lau et al 2021)? A consistent description of viscosity must consider deformation at the microscopic scale from observations on mantle xenoliths (Chatzaras and Kruckenberg 2021) and laboratory experiments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…van der Wal et al 2013). In general, viscosity can be seen as dependent on the frequency of loading (Lau et al 2021). What viscosity is representative for which mantle process in Antarctica and how can they be integrated?…”
Section: How Does Lithospheric Thickness Vary Across Antarctica?mentioning
confidence: 99%
“…These ranges of values reflect typical spatially-averaged estimates for the entirety of Greenland and Antarctica 28 31 . Note that this lithosphere thickness is not equivalent to T e ; it instead describes the thickness of an idealised elastic layer above the viscoelastic mantle appropriate for ice age timescales 32 . For the above range of mantle viscosities, the timescale required for the residual disequilibrium to decay by a factor of 1/5 e from its post-LGM peak value and thereby reach approximate steady state varies from 30 to 70 kyr.…”
Section: Methodsmentioning
confidence: 99%